COVID-19 Vaccine Hesitancy among the Population of Quetta—Associated Beliefs and Barriers - Misbah, Samreen; Mashhadi, Syed Fawad; Ilyas, Hassan; Bilal, Muhammad; Zia, Saad; Amjad, Hamza (Pakistan Armed Forces Medical Journal, 2024)
Objectives: This study aimed to determine the prevalence of hesitancy towards COVID-19 vaccination among the adult population of Quetta and the likelihood predictors of hesitancy towards COVID-19 vaccination.Study Design: Analytical cross-sectional study.Place and Duration of Study: Study was conducted at Quetta, from Nov 2021 to May 2022.Methodology: A total of 396 individuals participated in the study. Along with socio-demographic details, participants responded to the COVID-VAX scale and questions from WHO determinants of vaccine-hesitancy. A relationship was modelled between WHO determinants of vaccine-hesitancy, socio-demographic characteristics and vaccine-hesitancy using logistic regression.Results: Results showed that majority of individuals were vaccine-hesitant (67.2%). The final model obtained significant predictors among contextual influences as demonstrated past bad experiences on vaccination, non-belief in risking their own and family’s health for being non-vaccinated and negative influences by an influential person. Among individual influences,knowledge about someone having bad experiences to vaccines, confusion about scheduling of vaccines, lack of trust in the healthcare system and provider, disbelieving in immunization as a social norm and concerns regarding vaccine. Among factors directly related to vaccine/vaccination, difficult vaccination schedule, fear of pain/needles, and non-willingness to pay for vaccination were found as significant predictors of the COVID-19 vaccine-hesitancy (p-value